Desenvolvimento de membranas de pectina/quitosana e estudos de adsorção de íons Cu (II) - Martins, Jéssica Guerreiro (2019)
The development of durable materials based on polysaccharides has been a challenge due to low water stability. Therefore, in this work, through an unpublished methodology, we proposed the development of durable and resistant polymeric membranes. The pectin and chitosan-based membranes (PT/QT) were produced by using polymeric blends obtained in HCl 0,10 mol L–1 prepared in different ratios PT/QT (w/w). Physical hydrogels (PECs – polyelectrolytes complexes) without chemical crosslinking were processed with pectin (PT) excess in their structures, using PT with a high degree of O-methoxylation (56%). The membranes were characterized by infrared spectroscopy in total attenuated reflectance mode (FTIR–ATR), thermal analysis (TGA/DSC), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and analysis of mechanical properties. Stable and resistant membranes (with tensile strength in the range of 39 to 18 MPa) were obtained in the PT/QT (w/w) ratios at 14, 5 and 2. The membrane containing the highest mass content of PT (93%) in its structure (sample M (28-2)) was used as adsorbent material for Cu(II) ions. Kinetics and adsorption equilibrium studies showed that the kinetic model of pseudo-second-order and Sips isothermal model adjusted well to the experimental data, providing the highest coefficient determination values and lower deviations. The membrane M(28-2) presented a maximum adsorption capacity (qm) of 29.20 mg g–1 and adsorption/desorption cycles indicated that the material could be reused. After adsorption tests, the material containing Cu(II) ions can be applied in the biomedical field. The membrane with ions Cu(II) (M(28-2)/Cu) was cytocompatible for mesenchymal stem cells (MSCs) and had bacteriostatic activity against Escherichia coli. For the first time, durable and resistant PT/QT membranes containing PT in excess in their structures were developed, and then the membrane with a higher percentage of PT was used as an adsorbent agent for Cu(II) ions.